Decision Support System for Outstanding Students at SMA N 1 Belitang III Using the Profile Matching Method - Sultan Dwi Andri (Institute of Information Technology and Social Science (IITSS), 2023)
This study presents the design and development of a Decision Support System (DSS) to assist in determining the most eligible students for scholarship awards at SMA N 1 Belitang III. The system utilizes the Profile Matching method, which compares student attributes against ideal scholarship criteria to produce a ranked list of candidates. The process involves calculating competency gaps between students’ actual profiles and the ideal profile, assigning weights to each criterion, and aggregating these to generate overall suitability scores. Smaller gaps indicate closer alignment with the scholarship requirements. The resulting DSS enables school administrators to perform a transparent, efficient, and objective selection of scholarship recipients while minimizing human error in manual evaluation processes.